Engineering of chemical complexity - Mikhailov, Alexander S.; Ertl, G. (Gerhard) (World Scientific lecture notes in complex systems ;, 2013)
This review volume, co-edited by Nobel laureate G Ertl, provides a broad overview on current studies in the understanding of design and control of complex chemical systems of various origins, on scales ranging from single molecules and nano-phenomena to macroscopic chemical reactors. Self-organizational behavior and the emergence of coherent collective dynamics in reaction-diffusion systems, reactive soft matter and chemical networks are covered. Special attention is paid to the applications in molecular cell biology and to the problems of biological evolution, synthetic biology and design of artificial living cells. Starting with a detailed introduction on the history of research on complex chemical systems, its current state of the art and perspectives, the book comprises 19 chapters that survey the current progress in particular research fields. The reviews, prepared by leading international experts, yield together a fascinating picture of a rapidly developing research discipline that brings chemical engineering to new frontiers.